Simultaneous enhancement of photocatalytic bactericidal activity and strength properties of acrylonitrile-butadiene-styrene plastic via a facile preparation with silane/TiO2 - Kiatkittipong, Kunlanan; Jun, Wei Lim; Chin, Kui Cheng; Kiatkittipong, Worapon; Assabumrungrat, Suttichai (MDPI, 2020)
This work aims to enhance the photocatalytic antibacterial performance of plastics according to the JIS Z 2801:2010 standard, and to determine their mechanical properties by studying: (i) the influence of calcination on titanium dioxide (TiO2); (ii) modification with different TiO2 concentrations, and; (iii) the effect of silane as a coupling agent. Acrylonitrile-butadiene-styrene plastics (ABS) and Escherichia coli (E. coli) were chosen as the model plastic and bacteria, respectively. The 500 °C calcined TiO2 successfully provided the best photoantibacterial activity, with an approximately 62% decrease of E. coli colony counts following 30 min of exposure. Heat treatment improved the crystallinity of anatase TiO2, resulting in low electron-hole recombination, while effectively adsorbing reactants on the surface. ABS with 500 °C-calcined TiO2 at the concentration of 1 wt % gave rise to the highest performance due to the improved distribution of TiO2. At this point, blending silane coupling agent could further improve the efficacy of photoantibacterial activity up to 75% due to greater interactions with the polymer matrix. Moreover, it could promote a 1.6-fold increase of yield strength via increased adherent bonding between TiO2 and the ABS matrix. Excellent photocatalytic and material stability can be achieved, with constant photocatalytic efficiency remaining for up to five reuse cycles without loss in the yield strength.